Developing a Google Classroom Training Model for Elementary School Teachers - Dewi Ayu Sulistyaningrum; Hari Wibawanto; Eko Purwanti (Innovative Journal of Curriculum and Educational Technology, 2023)
Based on the need analysis, teachers had no idea on the implementation of online learning and lacked of information about choosing a proper learning platform for students during the COVID-19 pandemic. Therefore, the online learning did not run effectively since it was carried out using whatsapp application only to interact. Regarding this issue, this study aimed to improve teachers’ skills in the implementation of online learning using a google classroom platform with the ADDIE training model. Obviously, the design was an ADDIE Research and Development. Findings revealed that the google classroom training was able to improve teachers’ competency confirmed by the good validation results, namely 97% or very viable from a media expert, 94% or very viable from a material expert, and 86% of the respondents considered it very viable, so it can be concluded that the google classroom training model is effective to improve teachers’ competency. Besides, the ADDIE model can increase teachers’ performance and competency in designing interesting learning contents.